LEAF TRAITS OF THE INVASIVE SPECIES Bartlettina sordida (Less.) R.M. King NATURALIZED IN CIBODAS HIKING TRAIL, MT. GEDE PANGRANGO NATIONAL PARK, WEST JAVA, INDONESIA - Dwinda Mariska Putri; Decky Indrawan Junaedi; Vandra Kurniawan; Muhammad Efendi (Indonesian Journal of Forestry Research, 2022)
Cibodas Botanical Garden (CBG) maintains not only native plant species but also introduced plant species. Some of these have been naturalized from CBG to the adjacent Mt. Gede-Pangrango National Park (GPNP). One of the reported naturalized species is Bartlettina sordida. Understanding species traits will give information for the future management of B. sordida. This research investigates the distribution of B. sordida in the Cibodas hiking trail and studies leaf traits variation of this species along with an altitudinal change in the Cibodas hiking trail. Samples were collected along the Cibodas hiking trail from the entrance gate to the Cibeureum waterfall. At every survey location, we recorded B. sordida occurrences. In the sample plots we also collected leaf samples from detected B. sordida. The leaves were then fixated using the hands-free method to observed stomatal type, density, and size. The leaves were also treated for specific leaf area (SLA) measurements. Stomata size is significantly correlated along the altitudinal gradient. Stomata density is negatively correlated but not significant along the altitudinal gradient. Stomata size is positively correlated with SLA. These traits are related to water-efficient adapting to GPNP climate, which is very different from its natural habitat. The ability to adapt to altitudinal gradient helps B. sordida to dominate the Cibodas hiking trail.